Pemanfaatan Teks Feature Perjalanan sebagai Media dalam Pembelajaran Menulis Karangan Naratif - Nurjannah Gultom (Basastra, 2012)
Abstract: Featured is one kind of story in which an utterance of facts, events, event, or a history of the process with a written description, the process of formation or how it works. While the trip is a feature that tells the range feature a trip to a place that lures with a devious way. Feature written in chronological order based on the series of events. The experience of the event or events that the students read from the feature can be used as a basis or reference in the narrative essay writing. This is because the content or material is a form of narrative literature events or eventssimilar to the material contained in the text feature on the trip. Therefore, narrativeessay writing skills upgrading can be done with the use of media texts travelfeature. Keywords: utilization- narration-travel feature text